A curious new Coenosia Meigen, 1826 (Diptera, Muscidae) from Mariepskop, Mpumalanga, South Africa - Burgert S. Muller (African Invertebrates, 2019)
A new species of Coenosia Meigen, 1826 is described, C. flagelliseta sp. nov., belonging to a new aberrant group with apically globular orbital setae, previously only known from male specimens in two species. A female from this unique group is also described for the first time, having tergite 6 of the ovipositor atypical for the Coenosiini. The affinities of the group and the species within are discussed.